CHA2DS2-VASc Score Is Associated With Prognosis in Patients With Acute Ischemic Stroke Without Atrial Fibrillation - Mingjuan Song, MM; Xu Chen, MD (Texas Heart Institute Journal)
Background: Although the prognostic value of the CHA2DS2-VASc (congestive heart failure, hypertension, age ≥75 years, diabetes mellitus, prior stroke or transient ischemic attack, vascular disease, age 65-74 years, and female sex) scoring system in patients with stroke has been explored in several studies, a research gap exists in its application, especially in patients without atrial fibrillation (AF). Methods: This study investigated the association between CHA2DS2-VASc score and prognosis at 1 year in patients with acute ischemic stroke (AIS) who do not have AF. A total of 993 patients with AIS but without AF were recruited between January 2019 and December 2022. Patients were categorized into high-risk (CHA2DS2-VASc score, >2; n = 424), moderate-risk (CHA2DS2-VASc score, 2; n = 218), and low-risk (CHA2DS2-VASc score, 0-1; n = 351) groups. The primary outcome was major adverse cardiac events (MACE) at 1 year after index AIS. Multivariate Cox regression analyses evaluated the prognostic value of CHA2DS2-VASc scores after controlling for potential confounding factors. A sensitivity analysis was performed based on 3 CHA2DS2-VASc groups generated using propensity score matching. Results: The rate of MACE during 12-month follow-up was statistically significantly higher (P < .01) in patients with a CHA2DS2-VASc score greater than 2 (34.7%) than in patients with a score of 2 (23.9%) or of 0 or 1 (14.8%). Multivariate Cox regression models indicated that, compared with a CHA2DS2-VASc score of 0 or 1, the hazard ratio (HR) of MACE occurrence was 3.22 (95% CI, 1.93-5.37; P < .01) for a CHA2DS2-VASc score greater than 2 and 1.92 (95% CI, 1.24-2.98; P < .01) for a CHA2DS2-VASc score of 2. When included in the Cox regression model as a continuous variable, the CHA2DS2-VASc score remained strongly associated with higher risks of MACE (HR, 1.19 [95% CI, 1.11-1.26]; P < .01), all-cause mortality (HR, 1.14 [95% CI, 1.05-1.23]; P < .01), and recurrent stroke (HR, 1.15 [95% CI, 1.06-1.256]; P < .01). Sensitivity analyses based on populations generated by propensity score matching yielded similar results. Conclusion: The CHA2DS2-VASc score effectively predicts MACE in patients with AIS but without AF, providing more accurate risk stratification.